Efficacy and adverse reaction management of oncolytic viral intervention combined with chemotherapy in patients with liver metastasis of gastrointestinal malignancy - Jie Zhang; Jie Zhang; Qianyun He; Dongliang Mao; Chen Wang; Lei Huang; Lei Huang; Mei Wang; Jun Zhang (Frontiers in Oncology, 2023)
BackgroundThe liver is a key target organ for colorectal and gastric cancer metastasis. One of the challenges in the treatment of colorectal and gastric cancers is the management of liver metastasis. This study aimed to investigate the efficacy, adverse effects, and coping strategies of oncolytic virus injection in patients with liver metastases of gastrointestinal malignancies.MethodsWe prospectively analyzed patients treated at Ruijin Hospital affiliated with Shanghai Jiao Tong University School of Medicine from June 2021 to October 2022. 47 patients with gastrointestinal cancer liver metastasis were included in the study. The data, including clinical manifestations, imaging, tumor markers, postoperative adverse reactions, psychological intervention, dietary guidance, and adverse reaction management were evaluated.ResultsOncolytic virus injection was successful in all patients, and no drug injection-related deaths occurred. The adverse effects, such as fever, pain, bone marrow suppression, nausea, and vomiting, were mild and resolved subsequently. Based on the comprehensive intervention of nursing procedures, the postoperative adverse reactions of patients were effectively alleviated and treated. None of the 47 patients had any puncture point infections, and the pain caused by the invasive operation was relieved quickly. After 2 courses of oncolytic virus injection, postoperative liver MRI showed 5 partial remissions, 30 stable diseases, and 12 progressive diseases in target organs.ConclusionInterventions based on nursing procedures can ensure the smooth treatment of recombinant human adenovirus type 5 in patients with liver metastases of gastrointestinal malignant tumors. This is of great importance for clinical treatment and significantly reduces patient complications and improves the patient’s quality of life.